Chordoma, An Incidental Finding in A Patient with Low Back Pain and Urinary Incontinence: A Case Report - Ebere, Duru Ndubuisi; Okechukwu, Okwara Blasius; Chidi, Enemuo Vincent; Blessing, Eze Chinonso; Amaechi, Ugbala (American Journal of Health, Medicine and Nursing Practice, 2025)
Purpose: A chordoma is a rare mesenchymal tumour that occurs in the midline from clivus to sacrum.It is thought to originate from transformed remnants of notochord and has a prediletion for axial skeleton. A chordoma biological behavior is characterized by a slow aggressive local growth with a low tendency in metastasizing to distant sites including the lungs, bone, soft tissues, lymph nodes, liver and skin. Materials and Methods: We report an incidental finding of a case of lumbar chordoma in a 48-year old man who presented with a 7-year history of low back pain and urinary incontinence after a fall from a two storey building. At presentation, we made a diagnosis of traumatic neurogenic bladder but magnetic resonance imaging scan of lumbosacral spine revealed retropulsed collapsed 1st lumbar vertebra with cord compression. Findings: Spinal decompression done by the removal of the caseous material which was sent to histology revealed the diagnosis of chordoma. The epidemiology, clinical evaluation, diagnostic imaging and treatment modalities have been discussed with review of existing literature. Implications to Theory, Practice and Policy: It is important to have high index of suspicion of chordoma on any patient who presents with low back pain and urinary incontinence.